The Global Financial Crisis and Performance of the Indian Corporate Sector: A Firm Level Analysis - Saji, T. G.; Harikumar, S.; C., Mohammed Kasim (Indian Journal of Finance, 2013)
The U.S. financial crisis has made its upshots on both developed and developing economies of the world. However, India did not face a full - blown recession, but only experienced an economic deceleration, which is normally considered as a temporary phenomenon. Analysis of the financial parameters of corporate India revealed intersectoral as well as intrasectoral differences among them in respect of their financial fundamentals during the period of crisis, which could be attributed to many factors. The Banking sector found an opportunity for growth during the period of crisis, the credit of which goes to wise and judicious policies of the central bank of the country. The Automobile and construction sector were hit most adversely by the crisis due to their high capital intensive nature and stringent measures taken by the lending institutions by cutting back of credit to individuals for adding luxuries to their personal lives. Our IT industry is more exposed to the U.S. and European markets; hence, the financial crisis in these advanced economies affected the export earnings of this sector. However, sharp depreciation of the Rupee helped them to compensate in aggregate what they lost due to the crisis in the global market. Domestic market orientation and not being very capital-intensive are among the factors that insulated the FMCG sector from the downturn. The degree of shock exerted by the global financial turmoil on the performance of the Indian corporate sector was also not the same. While some companies under a particular sector were severely hit by the crisis, fundamentally strong companies could unshackle themselves from it.